1985
DOI: 10.1161/01.res.57.5.788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hemorrhage on renal nerve activity in conscious dogs.

Abstract: SUMMARY. We studied the effects of slow continuous hemorrhage (0.5 ml/kg per min) on measurements of arterial and left atrial pressures, and renal nerve activity in conscious dogs with all reflexes intact, or after sinoaortic baroreceptor denervation, cardiac denervation, or sinoaortic baroreceptor denervation plus vagal denervation. In intact dogs, mean arterial pressure remained relatively constant at 101 ± 4 mm Hg until 20 ± 4 ml/kg of hemorrhage, when renal nerve activity increased by 211 ± 53%. At 39 ± 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 18 publications
5
38
1
1
Order By: Relevance
“…62 Therefore, it is possible that the cardiopulmonary volume receptor is unloaded, and the renal sympathetic nerve is then reflexively activated. 63 Consistent with this, an increase in the central blood volume with no effect on the total blood volume, induced by head-out water immersion, which is known to reduce renal sympathetic nerve activity via the cardiopulmonary volume receptor, 64,65 significantly improves the renal excretory function. 66 Increased hepatic portal pressure is the other factor responsible for the increased renal sympathetic nerve activity.…”
Section: Liver Cirrhosismentioning
confidence: 63%
“…62 Therefore, it is possible that the cardiopulmonary volume receptor is unloaded, and the renal sympathetic nerve is then reflexively activated. 63 Consistent with this, an increase in the central blood volume with no effect on the total blood volume, induced by head-out water immersion, which is known to reduce renal sympathetic nerve activity via the cardiopulmonary volume receptor, 64,65 significantly improves the renal excretory function. 66 Increased hepatic portal pressure is the other factor responsible for the increased renal sympathetic nerve activity.…”
Section: Liver Cirrhosismentioning
confidence: 63%
“…in the apex of the heart) meet at the end of systole. The reflex may also originate in receptors within the pulmonary vessels 71 or the central veins. 72 These possibilities are not mutually exclusive and each may contribute to generate a vasovagal syncope leaving its specific origin unknown.…”
Section: Echocardiography and The Bezold-jarish Reflexmentioning
confidence: 99%
“…Experiments in animals have demonstrated that despite bilateral vagotomy or total cardiac denervation, sympathetic nerve activity falls (in a manner reminiscent of neurally mediated syncope) during hypotensive hemorrhage (11). In humans, neurally mediated hypotension and bradycardia with preceding sympathetic withdrawal have been similarly observed in patients with intact and with denervated ventricles (i.e., heart transplant patients) (12,13).…”
Section: Introductionmentioning
confidence: 99%